1997
DOI: 10.1089/aid.1997.13.695
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydronaphthalene Lignan Compounds as Potent Anti-HIV Type 1 Agents

Abstract: Anti-HIV-1 activity of tetrahydronaphthalene (THN) derivatives of lignan compounds was studied. THN derivatives prevented cell death caused by HIV-1 infection in MT-4 cells. They also inhibited giant cell formation by HIV-1 in Sup-T1 cells, and p24 production in HIV-1-infected H9 cells. The 50% effective concentration (ED50) of the most active compound, 1737 [5,6,7-trimethoxy-4-(3,4,5-trimethoxyphenyl)-1,3,3a,4,9,9a-hexahydron aphtho[2,3-c]thiophene], for inhibition of the cytopathic effects of HIV-1 infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…For example, HIV-1 group O strains are de novo resistant to current NNRTIs (10), but these viruses are susceptible to CAPmediated antiviral activity (18). In the present study, we have demonstrated that CAP is effective in inhibiting infection by HIV-1 strain A17, which is highly resistant to UC781 and other NNRTIs (15,32), suggesting that CAP can be used for preventing sexual transmission of NNRTI-resistant variants. Furthermore, UC781 has no documented activity against other STD pathogens.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For example, HIV-1 group O strains are de novo resistant to current NNRTIs (10), but these viruses are susceptible to CAPmediated antiviral activity (18). In the present study, we have demonstrated that CAP is effective in inhibiting infection by HIV-1 strain A17, which is highly resistant to UC781 and other NNRTIs (15,32), suggesting that CAP can be used for preventing sexual transmission of NNRTI-resistant variants. Furthermore, UC781 has no documented activity against other STD pathogens.…”
Section: Discussionmentioning
confidence: 58%
“…The HIV-1 strain A17, a variant of HIV-1 IIIB , is highly resistant to inhibition by NNRTIs, including pyridinone derivatives, BI-RG-587, and TIBO (tetrahydroimidazo[4,5,1-jk][1,4]-benzodiazepin-2-one) compounds (15,32). Resistance results from mutations at amino acids 103 (K3N) and 181 (Y3C) in the viral RT.…”
Section: Combination Of Cap With Uc781 Is Synergistic Against Hiv-1 Imentioning
confidence: 99%
“…The origins of HIV-1(III B ), HIV-1(NL4.3) (1, 35), HIV-2(ROD), HIV-2(EHO) (4,36), and simian immunodeficiency virus strain MAC 251 [SIV(MAC 251 )] (7, 35) have been described previously. The compounds were evaluated for their inhibitory effects against the replication of a variety of mutant HIV strains in MT-4 cells, such as nucleoside reverse transcriptase inhibitor (NRTI)-resistant strains (24,27), nonnucleoside reverse transcriptase inhibitor (NNRTI)-resistant strains (15,31), a protease-resistant strain (5), an L-708,906-resistant strain (14), and an L-870,810-resistant strain (20). The MK-0518-resistant strain harboring G140S and Q148H (37,39) was generated through site-directed mutagenesis (26) Drug susceptibility assay.…”
Section: Methodsmentioning
confidence: 99%
“…A 30 % inhibition of cell growth relative to control cultures was considered significant. The 50 % inhibitory concentration (IC 50 ) and the 50 % cytotoxic concentration (CC 50 ) were determined by interpolation from the plots of percent inhibition versus concentration of compound.The test for activity against HIV-1 was performed in MT-4 cell cultures infected with either wild-type HIV-1 (strain IIIB [26]) or NNRTI resistant HIV-1 (strain N119 [27], strain A17 [28,29].…”
Section: Inhibition Of Hiv-1 Replicationmentioning
confidence: 99%